Penerapan model pembelajaran the power of two untuk meningkatkan minat dan hasil belajar - Hasyim, Hasyim; Wulandari, Suci; Syahputra, Edy (Indonesian Institute for Counseling, Education and Therapy (IICET), 2024)
This study aims to analyze the effect of the application of the power of two type cooperative learning model on learning interest and learning outcomes of class XI OTKP students at SMK PAB 2 Helvethia, as well as to determine the relationship between learning interest and student learning outcomes. The research method used was purposive sampling, with a sample of one class consisting of 32 students. Data collection was done through questionnaires and tests, which included pre-test and post-test. This research took place during one semester. The results of the analysis showed a significant increase in learning interest, with an average learning interest score of 79.84. The average pre-test and post-test scores were 71.15 and 86.62 respectively. The results of hypothesis testing using t-test showed that the t-count for learning interest was 10.668 (t-table = 1.69), while for pre-test and post-test, the t-count was 5.492 (t-table = 1.69). The correlation test resulted in an r-count of 0.620 (r-table = 0.349), which indicates a positive and significant relationship between learning interest and learning outcomes.The conclusion of this study is that the application of the power of two type cooperative learning model has a positive and significant influence on students' interest in learning and learning outcomes. The findings provide practical implications for teachers and educational institutions in applying learning methods that can effectively improve students' interest and learning outcomes.